1996
DOI: 10.1021/jp953387e
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Properties of PolyanilineIsotope Effects

Abstract: The effect of polyaniline deuteration on the Raman spectra of this polymer has been studied in detail. Four types of samples have been prepared:  nondeuterated polyaniline, polyaniline deuterated selectively on the ring, polyaniline deuterated selectively on nitrogen, and polyaniline deuterated both on the ring and on the nitrogen. Selective deuteration allowed for experimental verification of the Raman modes assignment proposed for different types of polyaniline. In particular, the contribution of C−H bending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
186
0
6

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 284 publications
(210 citation statements)
references
References 29 publications
18
186
0
6
Order By: Relevance
“…Alguns picos Raman característicos da POMA-ES são: 577 cm -1 atribuído à deformação da amina no plano, 1356 cm -1 atribuído ao cátion radical (estiramento C-N + ) e 1597 cm -1 atribuído ao estiramento C-C do anel benzeno. A Tabela 1 traz os picos Raman da base e do sal de POMA esmeraldina, e suas respectivas atribuições, as quais são "atribuições tentativas" baseadas nas referências [30][31][32][33][34][35] que se referem à PANi.…”
Section: Caracterização Vibracional E Morfológica Por Microespectroscunclassified
“…Alguns picos Raman característicos da POMA-ES são: 577 cm -1 atribuído à deformação da amina no plano, 1356 cm -1 atribuído ao cátion radical (estiramento C-N + ) e 1597 cm -1 atribuído ao estiramento C-C do anel benzeno. A Tabela 1 traz os picos Raman da base e do sal de POMA esmeraldina, e suas respectivas atribuições, as quais são "atribuições tentativas" baseadas nas referências [30][31][32][33][34][35] que se referem à PANi.…”
Section: Caracterização Vibracional E Morfológica Por Microespectroscunclassified
“…For the title compound the υ CN mode is observed at 1203 cm . The out-of-plane CH deformation bands ω CH are expected in the range 740 -990 cm −1 [21]. As seen from Table 3, the DFT-B3LYP calculation give wave numbers at 863,829 cm −1 .…”
Section: Assignments Of the Vibration Modesmentioning
confidence: 79%
“…The absorption appears at higher frequencies than the corresponding absorption of aliphatic amines because the force constant of the C-N bond is increased by resonance with the ring. Louran et al [21] reported a value at 1220 cm −1 for υ CN for polyaniline. For the title compound the υ CN mode is observed at 1203 cm .…”
Section: Assignments Of the Vibration Modesmentioning
confidence: 99%
“…Observa-se na Figura 58 que os nanotubos formados apresentam estrutura morfológica bem mais definida sem a presença de uma grande quantidade de estruturas granulares entre os mesmos. [199][200][201][202].…”
Section: Síntese E Caracterização Morfológicaunclassified
“…A banda localizada na região entre 1510-1480 cm -1 é muito importante na caracterização da estrutura polimérica da PANI, uma vez que esta região está associada aos dois tipos de portadores de carga da PANI, polarons e bipolarons, podendo indicar a população relativa entre os mesmos [200,201,203]. Uma análise detalhada desta importante região do espectro tem sido reportada para materiais híbridos de PANI/hexaniobato e tem mostrado que as populações relativas polarons/bipolarons são sensíveis à interação entre cadeia polimérica e a alta acidez da superfície do hexaniobato [204][205].…”
Section: Síntese E Caracterização Morfológicaunclassified